Oxaliplatin plus leucovorin and 5-fluorouracil (FOLFOX-4) as a salvage chemotherapy in heavily-pretreated platinum-resistant ovarian cancer - Vincenza Conteduca; Giorgia Gurioli; Lorena Rossi; Emanuela Scarpi; Cristian Lolli; Giuseppe Schepisi; Alberto Farolfi; Delia De Lisi; Valentina Gallà; Salvatore Luca Burgio; Cecilia Menna; Andrea Amadori; et al. (BMC Cancer, 2018)
Abstract Background The purpose of this study was to evaluate the clinical impact of oxaliplatin, leucovorin, and 5-fluorouracil (FOLFOX-4) chemotherapy in terms of the response rate, progression-free/overall survival (PFS/OS) and safety profile in patients with heavily pretreated recurrent epithelial ovarian cancer. Methods Clinical data were reviewed in 29 patients who received FOLFOX-4 as more than third-line chemotherapy, consisting of 85 mg/m2 of oxaliplatin, 200 mg/m2 of leucovorin, and bolus 400 mg/m2 on day 1 of 5-fluorouracil, followed by a 22-h infusion of 600 mg/m2 of 5-fluorouracil for 2 consecutive days every 3 weeks. We also compared the efficacy and toxicity of FOLFOX-4 with that of topotecan, a standard treatment, given at a dosage of 1.5 mg/m2 every three weeks in 26 patients. Results The median age of enrolled patients was 60 years (range 33 to 85). A median of 4 cycles (range 1–17) of FOLFOX-4 were administered. Complete response and partial response were observed in one (3.5%) and 5 (17.2.2%) patients, respectively, while stable disease was reported in 8 (27.6%) patients. Among all patients, grade 3–4 anemia, neutropenia, and thrombocytopenia were observed in 0 (0%), 5 (17.2%), and 3 (10.3%) cases, respectively. Grade 3–4 fatigue was recorded in one (3.4%) patient and diarrhea in 2 (6.9%). Median PFS and OS were 2.8 months [95% confidence interval (CI) 1.7–4.9] and 6.2 months (95% CI 2.4–14.6), respectively. No significant differences in terms of efficacy and toxicity were observed between patients receiving FOLFOX-4 and those treated with topotecan. Conclusions The FOLFOX-4 regimen would seem to obtain similar survival rates to those of standard therapy with topotecan in platinum-resistant ovarian cancer. Further randomized trials are warranted to confirm our findings.